TabletTeach : opportunity analysis for a new educational technology product - Sawhney, Mohanbir S., (SAGE knowledge. Cases., 2016)
In May 2013, Jack Russo, a Chicago-based tech entrepreneur, had to choose one of four possible product concepts to use as the starting point for his new K-8 educational learning company, TabletTeach LLC. At the time, the K-12 education market in the United States was experiencing major disruption due to print-to-digital transformation, new Common Core State Standards (CCSS), new standardized tests aligned to the Common Core and increasing pressure from parents for schools to incorporate technology in their children's learning. This study explains how he set about meeting these challenges.